Deliberative Debates in Investors Penetration Area: A Case Study of Village Deliberation by Village Consultative Board (BPD) in Caturtunggal Village, Yogyakarta - Abd. Hamid, Husen Wijaya (Political Science Program, Universitas Negeri Semarang, 2018)
This study focuses on deliberative democracy practices in Caturtunggal village, specifically in the sub-village (dusun) of Seturan, Karangwuni, and Ambarukmo. The study assesses the quality of deliberation in these dusun by applying the three out of five indicators of deliberative democracy theory by Fishkin (2009), namely information, subtantantive balance, and equal consideration. This study deploys qualitative descriptive method and case-study approach with in-depth interview as the main data gathering technique. This deliberation has putVillage Consultative Board (BPD) period of 2013-2019 as a mediator and to consider arguments and deliberative results. Based on the indicators which proposed by Fishkin, Seturan and Ambarukmo are categorized for having semi-ideal deliberation, meanwhile Karangwuni is categorized as not ideal. The study also finds elite capture practices in Seturan and Karangwuni, but they do not impact significantly.